The Role of Women's Organizations in Preventing Terrorism (Counter-Radicalism Action Study by PW Fatayat NU West Java) - Hikmawati, Risma; Hannah, Neng; Rochmawati, ida; Wahyudin, Dedih (Universitas Syiah Kuala, 2024)
Fatayat NU as an Islamic women's community organization has participated in peace actions and encouraged society to have strong resilience from exposure to extremism doctrines. The research aims to describe the role of women's organizations, namely PW Fatayat NU West Java, with the object being women and children exposed to radicalism and also considering the suitability of their activities with the programs that have been launched by the Indonesian government as stated in Law of the Republic of Indonesia Number 5 of 2018. Therefore, this research seeks to analyze the contribution of women's mass organizations, namely PW Fatayat NU West Java, in activities to prevent violent extremism against women and children to state programs, in the 2020-2021 period. The research method is qualitative with field studies, and the results of the data obtained are then analyzed using descriptive analytical methods. The research results showed that efforts to implement counter-radicalism by PW Fatayat NU West Java were considered to be in accordance with the objectives of counter-radicalism based on the Law of the Republic of Indonesia, Article 43 C, Number 5 of 2018, and in the type of activity, PW Fatayat NU West Java had implemented three types of counterradicalism, namely counter-narrative, counter-propaganda and counter-ideology. These three types of efforts have helped raise awareness, strengthen networks, clarify information, provide important insight and knowledge regarding the complexity of the issue of radicalism and the things that accompany it, and have encouraged joint programs in prevention and assistance efforts for women and children who are exposed to radicalism.